ISLAMIC INSURANCE AND CONVENTIONAL INSURANCE : WHAT’S THE DIFFERENCE? - Ade Eriyanto; Faiz Mazda Niamy; Zenila Febi Sania; Rinda Asytuti (JASIE, 2023)
The aim of this research is to describe the differences between sharia insurance and conventional insurance, namely by looking at the principles, objectives and legal basis of the two types of insurance. The method used in this research is a qualitative method with a literature study approach. The data used in this research comes from literature from website articles, books, previous journals, and other related documents related to the research. The results of this research show that sharia insurance and conventional insurance have differences in several aspects, especially in terms of objectives and principles. Islamic insurance is based on the principles of Islamic law, while conventional insurance operates based on conventional financial principles. Keywords : Islamic Insurance; Conventional Insurance